Enhancing RNAi Efficiency to Decipher the Functional Response of Potential Genes in Bemisia tabaci AsiaII-1 (Gennadius) Through dsRNA Feeding Assays - Kaur, Ramandeep; Gupta, Mridula; Singh, Satnam; Joshi, Neelam; Sharma, Abhishek (Frontiers in Physiology, 2020)
The whitefly Bemisia tabaci is a global invasive pest that causes substantial losses to agricultural crops worldwide either by feeding and transmitting plant viruses. Management of this pest with insecticides is the biggest challenge due to developed resistance. RNA interference (RNAi) has been shown to be a promising strategy to control whitefly and to limit plant viruses spread. The present study targets ten potential genes (AQP, CAL, CYCP, K-1, Hsp20, Hsp 40, Hsp70, Hsp90, SNF and IAP) of whitefly that have been implicated in various vital physiological functions and mediate plant virus transmission. The present study compares the knockdown efficiency of different genes targeted through feeding dsRNAs, dsRNA(s) incorporated in dsRNA of dsRNAse (dsdsRNase) and dsRNA-CQD nanoconjugates. The studies revealed that feeding of dsRNA (40µg/ml sucrose diet) of the target gene(s) either conjugated with CQD or along with dsRNA against dsRNase (dsdsRNase) (40µg/ml sucrose diet) enhanced the RNAi efficiency by 24-89% compared to whiteflies fed with only dsRNA (naked dsRNA against same target gene) as well as control (dsRNA against Green fluorescent protein gene- dsGFP).